PERANCANGAN SISTEM INFORMASI PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN KUBU RAYA - Ariza, Indradwita (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2014)
Deliberation sub  district development plan  is one way to increase the impact of development. Results of deliberation sub  district development planwill be discussed again in the unit forums then compiled and refined into a work plan. Planning  Information Planning is an application development used to improve the performance deliberation sub  district development plan  and  unit forums on Bappeda  Kubu Raya and  participant  from various regions and  unit forums. In practice often found several obstacles such as the absence so information systems can assist in the implementation of this activity. The author builds information systems development using the  Technology Acceptance Model  (tam)  and Structural Equation Models  (sem)  in the design and establishment of web applications. This site will be operated by an employee and become operator of each district or unit forum. The operator will get an account from  Bappeda Kubu Raya,  then  the operator of a sub district or unit forum can use the application to include the proposed activities of the sub district or unit forum. Operators who use these web applications can participate without having to meet in a room. Results can also be seen by web visitors.